The Antiplaque Efficacy and Effectiveness of Activated Charcoal Toothpaste of Elaeis guineensis in Smokers - Uce Lestari; Syamsurizal Syamsurizal; Yustika Trisna (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Plaque on the teeth of smokers comes from cigarette smoke tar that settles on the surface of the teeth and roots of the teeth, causing the tooth surface to become rough and easier to stick with food debris and germs that will react making it easier for plaque to form. This study was aims to determine the safety and effectiveness of removing plaque in palm shell activated charcoal toothpaste with a concentration of 12% calcium carbonate combination of 25%. The content of calcium carbonate as an abrasive against the dental plaque of active smokers. The method used was measurement the plaque index score according to Turesky before and after using toothpaste on 20 panelists of active smokers. The decrease in plaque index in the use of toothpaste by using Wilcoxon's non-parametric statistical test, namely P = 0.000 (Sig <0.05). The results showed that toothpaste in the first week was able to reduce dental plaque by 59% compared to positive control by 45% and without activated charcoal by 34%. Toothpaste and positive control in the second week were able to remove dental plaque by 100%, while toothpaste without activated charcoal and calcium carbonate was only able to remove dental plaque by 68%. It can be concluded that palm shell activated charcoal toothpaste with a concentration of 12% combined with 25% calcium carbonate is safe and effective in removing plaque on the teeth of smokers.Keywords: dental plaque, efficacy, palm shells